2024
DOI: 10.1001/jamainternmed.2023.6279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Personalized Risk-Reduction Strategies on Cognition and Dementia Risk Profile Among Older Adults

Kristine Yaffe,
Eric Vittinghoff,
Sascha Dublin
et al.

Abstract: ImportanceModifiable risk factors are hypothesized to account for 30% to 40% of dementia; yet, few trials have demonstrated that risk-reduction interventions, especially multidomain, are efficacious.ObjectiveTo determine if a personalized, multidomain risk reduction intervention improves cognition and dementia risk profile among older adults.Design, Setting, and ParticipantsThe Systematic Multi-Domain Alzheimer Risk Reduction Trial was a randomized clinical trial with a 2-year personalized, risk-reduction inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Nonetheless, a recent study involving 172 older adults aged 70 to 89 years, each with at least two dementia risk factors targeted by the intervention, revealed that a 2‐year, personalized, multidomain intervention resulted in enhanced cognitive function. 28 This result implies that initiating interventions is not too late and highlights the potential importance of personalized or tailored interventions among older adults in the late stages of life.…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, a recent study involving 172 older adults aged 70 to 89 years, each with at least two dementia risk factors targeted by the intervention, revealed that a 2‐year, personalized, multidomain intervention resulted in enhanced cognitive function. 28 This result implies that initiating interventions is not too late and highlights the potential importance of personalized or tailored interventions among older adults in the late stages of life.…”
Section: Discussionmentioning
confidence: 95%
“…Ultimately, tools like DunedinPACE could prove useful to clinicians treating cognitively intact older adults with subjective complaints, uncertain ADRD biomarker classifications, and ambiguous trajectories of cognitive decline. In the near term, DunedinPACE and related tools could enhance risk stratification for intervention studies 49 . Finally, the connections between pace of aging and cognitive decline identified in our results suggests that interventions that slow pace of aging may also contribute to neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Improving engagement in care would reduce competing HIVrelated mortality, which could, however, further increase the lifetime risk of developing AAD, unless interventions to reduce AAD risk are made available and accessible. Interventions to counter disadvantageous social determinants of health, reduce tobacco use, and treat substance use disorder are, therefore, essential to improve life expectancy and reduce the lifetime risk of AAD among people aging with HIV, such as has been investigated in the general population [60]. A published cost-effectiveness analysis showed that interventions aimed at lowering vascular risk factors, such as treating hypertension and smoking cessation, could be cost-effective in reducing dementia among the general population [61].…”
Section: Lifetime Cumulative Incidence Of Aad (%)mentioning
confidence: 99%